Cultural Heritage Management Challenges: Historical Village of Huta Siallagan in Indonesia - Violina, JM Vivi; Kudumovic, Lana (O.D. IMS Vogosca, 2026)
Effective cultural heritage preservation requires a holistic approach, guided by management that integrates governance, planning (including disaster prevention, risk management, promotion, education, community involvement, awareness-raising, and sustainable tourism), financing, and implementation. Despite existing frameworks, many historical sites face conservation challenges, often stemming from gaps in planning and management. This study aims to define the cultural heritage management components for Huta Siallagan, a historical village in Indonesia, located on an island within the UNESCO Global Geopark of Lake Toba. The village has preserved its unique Batak cultural heritage retaining its natural setting, site layout, building structures, while intangible practices continue to be actively maintained. The study examined current legal status of the site through national and international legislative frameworks as well as its overall condition. Finding indicate that gaps remain in planning and management frameworks. The study concludes with recommendations for multi-level strategies and heritage management components to strengthen existing conditions and enhance sustainable development.
Keywords: Cultural Landscape; Historical Village; Cultural Heritage; Conservation Management Chall